Inhibition Experiments on Anaerobic Methane Oxidation - Alperin, Marc J. (1985)
Anaerobic methane oxidation is a general process important in controlling fluxes of methane from anoxic marine sediments. The responsible organism has not been isolated, and little is known about the electron acceptors and substrates involved in the process. Laboratory evidence indicates that sulfate reducers and methanogens are able to oxidize small quantities of methane. Field evidence suggests anaerobic methane oxidation may be linked to sulfate reduction. Experiments with specific inhibitors for sulfate reduction (molybdate), methanogenesis (2-bromoethanesulfonic acid), and acetate utilization (fluoroacetate) were performed on marine sediments from the zone of methane oxidation to determine whether sulfate-reducing bacteria or methanogenic bacteria are responsible for methane oxidation. The inhibition experiment results suggest that methane oxidation in anoxic marine sediments is not directly mediated by sulfate-reducing bacteria or methanogenic bacteria. Our results are consistent with two possibilities: anaerobic methane oxidation may be mediated by an unknown organism or a consortium involving an unknown methane oxidizer and sulfate-reducing bacteria.